IMPLIKASI INTRAKURIKULER KALIGRAFI DALAM PELESTARIAN SENI BUDAYA ISLAM DI MADRASAH TSANAWIYAH DARUN NAJAH KARANGPLOSO MALANG - Hilyah Ashoumi; Muhamad Masyhuri Malik; Siti Latifatul Maulidiah (LP2M Universitas Ibrahimy, 2022)
The implementation of calligraphy intracurricular activities that have been carried out at Madrasah Tsanawiyah Darun Najah Karangploso Malang so far still has the aim of preserving Islamic art and culture and supporting the potential of students, so far the learning process has been going well, but there is a need for a more specific study of the implications of these intracurricular activities in students who take part in this activity. The main problems in this research are as follows; (1) How is the implementation of calligraphy intracurricular learning at Madrasah Tsanawiyah Darun Najah Karangploso Malang? (2) What are the factors that encourage and inhibit calligraphy intracurricular learning in preserving Islamic cultural arts at Madrasah Tsanawiyah Darun Najah Karangploso Malang? (3) What are the implications of calligraphy intracurricular learning in preserving Islamic cultural arts at Madrasah Tsanawiyah Darun Najah Karangploso Malang? This research belongs to the type of qualitative research. In data collection techniques, researchers used interviews, observation, and documentation. Then the techniques in data analysis using data reduction, displaying data, and drawing conclusions. The results in this study are (1) Calligraphy learning at MTs Darun Najah including intracurricular learning which is carried out every Thursday for two hours once a week, which uses the talaqi system starting with learning tahsinul kitabah then khattul 'Arabi. (2) The motivating factors for students to take calligraphy intracurricular are improving Arabic writing, a clear learning system, and the creativity of teachers' approaches and learning strategies in teaching. The inhibiting factor is the unstable spirit of the students, and the lack of experts/teachers which results in long queues in the guidance of calligraphy assignments, facilities, and infrastructure. (3) The Implications in calligraphy intracurricular can preserve Islamic cultural arts, love art, participate in calligraphy competitions, and can practice the values ​​contained and implied in calligraphy learning including patience, maintaining cleanliness, responsibility, sami'na wa atho'na (obedient), and honest.